A SKILLFUL PEDAGOGICAL TRAJECTORY IN THE PROCESS OF CONTINUOUS PROFESSIONAL EDUCATION - Salimova Yulduz Ne'matovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: in this article , the system of continuing education is reflected in its essence and continuous training, approaches to developing the theoretical knowledge of future specialists on the basis of practical skills and field and innovative approaches to base competencies, and in general, the trajectory of a skilled pedagogical staff in the processes of non-ring vocational education.